Mineral resources in the age of climate adaptation and resilience. (6th October 2019) - Bleischwitz, Raimund
Abstract: This article discusses issues on resources availability to achieve climate adaptation and resilience for cities and infrastructures. In the age of climate change, there could be cascading failures through a range of infrastructure breakdowns. Direct and indirect damage costs could exceed what had been estimated in traditional risk assessments. This could be exacerbated through abrupt price peaks in international supply chains of minerals, and through events happening in remote parts of the world that affect extraction and vulnerable industries. The core argument made here is one of feedbacks: climate adaptation has significant resource implications, and how resources are being used will have implications on climate strategies. Industrial Ecology has a role to play assessing those interactions and providing a better grasp of the spatial dimension of material flows, partly to track those flows and align them to specific actors, and partly to address interlinkages across different flows and their stocks ('the resource nexus'). Methodological novelties are needed to better understand the resource base and the socio‐economic dimension, especially on innovations and transitions that can help to cope with the challenges ahead. Altogether this would enable research to establish an evidence base on sustainable materials to deliver parts of the UN Sustainable Development Goals (SDGs) and to reassess infrastructure assets and the mineral resources in the age of climate adaptation and resilience.